Naʾī ġazal ke sarokār - Muʿīnī, Maškūr (Maġribī Bangāl Urdū Akāḍmī, 2019)
Critical articles on contemporary Urdu ghazals. Study on 20th century Urdu ghazals
Includes bibliographical references (pages 187-200)
Keywords: Ghazals; Urdu; History and criticism.; Urdu poetry; 20th century; History and criticism.; Ghazals; Urdu; Urdu poetry